Mechanical properties analysis of non-pneumatic tire with gradient honeycomb structure - Tao Liu; Yaoji Deng; Keyu Lu; Hui Shen; Junjie Gong; Hong Li (Engineering Science and Technology, an International Journal)
Non-pneumatic tires have the advantages of high safety and high load-carrying capacity, and have a broad potential for engineering applications. In this paper, the effects of different gradient angles on the static and dynamic performance of honeycomb spoke structure are studied. First of all, according to different gradient and gradient-free Non-Pneumatic Tires (NPTs) are designed and the corresponding finite element models of non-pneumatic tires are established respectively. Then, the static mechanical properties of NPTs are analyzed, including the bearing capacity of NPTs and the stress distribution of NPT components. Finally, the dynamic mechanical properties of gradient-free and gradient NPTs are simulated. The stress characteristics and rolling characteristics of the gradient to the key components of NPTs under dynamic load are analyzed. The results show that different gradients have effects on the radial stiffness of the tire, the maximum stress distribution position of spokes, tire rolling characteristics, and the stress characteristics of other parts of NPTs. The research results provide guidance for the structure design and optimization of non-pneumatic tires.